Weight loss in a cardiovascular trial population identifies people at future risk of dementia. Issue 1 (30th August 2022) - van der Veere, Pieter; Hammami, Imen; Buck, Georgina; Greenland, Melanie; Offer, Alison; Nunn, Michelle; Whiteley, William; Bulbulia, Richard; Collins, Rory; Armitage, Jane; Mafham, Marion; Parish, Sarah; et al.
Abstract: Introduction: Populations at increased risk of dementia need to be identified for well‐powered trials of preventive interventions. Weight loss, which often occurs in pre‐clinical dementia, could identify a population at sufficiently high dementia risk. Methods: In 12, 975 survivors in the Heart Protection Study statin trial of people with, or at high risk of, cardiovascular disease, the association of weight change over 5 years during the trial with post‐trial dementia recorded in electronic hospital admission and death records ( n  = 784) was assessed, after adjustment for age, sex, treatment allocation, and deprivation measures. Results: Among the 60% without substantial weight gain (≤2 kg weight gain), each 1 kg weight loss was associated with a risk ratio for dementia of 1.04 (95% confidence interval, 1.02–1.07). Weight loss ≥4 kg and cognitive function below the mean identified participants aged ≥67 years with a 13% 10‐year dementia risk. Discussion: The combination of weight loss and high vascular risk identified individuals at high risk of dementia who could be recruited to dementia prevention trials.